Effect of graphite particle fillers on dielectric and conductivity properties of poly(NIPAM-co-HEMA) - Torgut, G.; Biryan, F.; Demirelli, K. (Indian Acad Sciences, 2019)
Copolymers of 2-hydroxyethyl methacrylate (HEMA) and N-isopropylacrylamide (NIPAM) in different ratios were prepared by free radical polymerization using 2,2 '-azobisisobutyronitrile as an initiator at 60 degrees C. The copolymers were analysed by Fourier transform infrared and proton nuclear magnetic resonance. Thermal behaviours were determined by thermogravimetric analysis and differential scanning calorimetry (DSC). DSC measurements showed that the glass transition temperature (Tg) of poly(HEMA) and poly(NIPAM) was 100 and 140 degrees C, respectively. Electrical properties (dielectric constant, dielectric loss and alternating current conductivity) of polymers and composites prepared with graphite were investigated by using an impedance analyser, in the range of 10-20 kHz. While the dielectric constant values vary from 3.3 to 4.01 for copolymers at 1 kHz, these values are increased about 10 times for composites doped with 10 wt% graphite. Similarly, the dielectric loss and conductivity values were fairly high for composites. The conductivity values of composites doped with 10 wt% graphite showed a significant increase and the insoluble polymer became semiconducting. It was observed that the electrical properties of graphite-added composites at different ratios (8, 9 and 10 wt%) increased with the increase in graphite ratio for all polymers. In addition, the direct current conductivity of composites doped with 10 wt% graphite was examined according to the temperature and the activation energy (Ea) values were calculated.
Keywords: Composites; conductivity; dielectric constant; graphite; polymer characterization; radical polymerization